Paradoxes of CEE management practices and culture: Selected papers from the 9th Eastforum Chemnitz - Irma Rybnikova (Technische Universität Chemnitz, Professur für Organisation und Arbeitswissenschaft, 2012)
[Contents] Irma Rybnikova: Editorial, p.3 - Gheorghe Alexandru Catana, Doina Catana: Conflict and cooperation inducer behaviors in Romanian organizations: followers'perception, p.6 - Alicja Miś: Theory and practice of talent management in Polish organizations, p.27 - Natalia Spiridonova: Clashes between Western Management and Eastern Reality, p.44 - Renata Krzykała-Schaefer, Anna Antczak: Cultural profile of Polish students. Directions of change and perspectives for managers, p.63
urn:nbn:de:101:1-20130111670
Keywords: 650